Institutions or geography: What explains more to trade policy for developing nations? - Saima Sarwarand; M. Wasif Siddiqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
This study attempts to develop a trade policy-growth nexus using political economy approach for world developing nations. Trade policy has been assumed as endogenous variable in whole analysis which means that many exogenous factors can have the effect on the policy choices in nations. Seven trade policy measures including policy based, outcome based, composite indices, and market based measures, have been covering the time span 1995-2013. Dynamic Panel Model has been estimated using an instrumental variable technique i.e. System Generalized Methods of Moment (SGMM). Findings of the model are confirming the importance of institutions and governance over geography in case of each trade policy proxy for developing nations. The policy recommendation on the basis of all these results is that neoliberal policies can be decisive for developing nations if integrated with good governance along with various political and economic institutions.
Keywords: 330; Trade policy; Political Economy; Bureaucracy; Geography; Panel Model